QUALITY CONTROL ANALYSIS OF PEW ENAMEL WIRE USING PARETO AND FISHBONE - Violentisca Hermanto, Jason Hermanto; Fitriani, Katlea (Management Department, Faculty of Economics and Business, Universitas Jambi, 2026)
PT Cakra Wire is a manufacturing company that produces enamel wire for various industrial applications, such as electric motors, transformers, and other electromagnetic devices. During the production process, the company faces quality issues and defective products, which potentially increase production costs and reduce process efficiency. Production data from January to February 2026 indicate that PEW type enamel wire exhibits a relatively high defect rate compared to other product types. This situation necessitates an analysis of the types of defects occurring and the factors contributing to their formation during the production process. The aim of this study is to identify the types of defects in PEW enamel wire, determine the dominant defect type, and analyze the underlying causes. A descriptive research design employing a mixed-methods approach was selected. Data collection involved observations, interviews, document analysis, and the evaluation of operational records regarding product defects from January to February 2026. The analysis was conducted using specific instruments from the